2004
DOI: 10.1086/424733
|View full text |Cite
|
Sign up to set email alerts
|

Atomic and Molecular Emission Lines from the Red Rectangle

Abstract: HD 44179 is the binary, post-asymptotic giant branch, central star of the Red Rectangle Nebula. Echelle spectra of the star have been obtained over a wavelength range from about 3800 to 10000 8 at a resolving power R ¼ 38; 000. A maximum S/ N of 850 was achieved near 6800 8. Fifty-seven identified atomic or ionic emission lines of 12 elements are detected in the star's spectrum, along with 76 emission lines of CH, CH + , or CN. Three other CN lines are also present in absorption. Fewer than 30 of these 136 lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 46 publications
5
52
1
3
Order By: Relevance
“…We also searched for molecular emission that previously has been identified in the Red Rectangle and/or in the ISM. In particular we looked for: H 2 (Rosenberg et al 2013), CN, CH, C 2 (van Dishoeck & Black 1989;Hobbs et al 2004;Wehres et al 2010), CH + (Carrington & Ramsay 1982;Hobbs et al 2004), C 3 (Maier et al 2001), NH (Hofzumahaus & Stuhl 1985) (Wu et al 2008;Vujisic & Pesic 1988). It is intriguing that the Red Square Nebula shows no signature of molecular emission lines other than CO, as well as emission lines of very large species such as PAHs and silicates.…”
Section: The Optical Spectrum: Molecules and Atomic Ionsmentioning
confidence: 99%
“…We also searched for molecular emission that previously has been identified in the Red Rectangle and/or in the ISM. In particular we looked for: H 2 (Rosenberg et al 2013), CN, CH, C 2 (van Dishoeck & Black 1989;Hobbs et al 2004;Wehres et al 2010), CH + (Carrington & Ramsay 1982;Hobbs et al 2004), C 3 (Maier et al 2001), NH (Hofzumahaus & Stuhl 1985) (Wu et al 2008;Vujisic & Pesic 1988). It is intriguing that the Red Square Nebula shows no signature of molecular emission lines other than CO, as well as emission lines of very large species such as PAHs and silicates.…”
Section: The Optical Spectrum: Molecules and Atomic Ionsmentioning
confidence: 99%
“…The cross-section for photo-destruction, however, indicated that the molecule is rather fragile and is destroyed very efficiently in the harsh radiation field of the central star. Wehres et al (2010) concluded that the C 2 lifetime in the nebula is too short given the slow outflow velocity (Van Winckel et al 1995;Hobbs et al 2004;Witt et al 2009;Wehres et al 2010) in the nebula and a replenishment (e.g., from a PAH reservoir) is needed in order to explain the appearance of the Swan-bands in several spectra. An active photochemistry is needed to account for this e.g., the break down of PAHs in a timescale of 10 3 -10 4 years, producing C 2 H 2 which is then quickly photolysed to C 2 .…”
Section: Chemistrymentioning
confidence: 99%
“…The Red Rectangle proto-planetary nebula itself has been found to be carbon rich (Waters et al 1998) and apart from the spatially resolved PAH emission in the nebula, identified molecules comprise besides C 2 also CH, CH + and CN (Balm & Jura 1992;Hobbs et al 2004). Also oxygen rich molecules have been identified like gas phase and solid state CO 2 (Waters et al 1998), OH (Reese & Sitko 1996) and CO isotopes (Waters et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This free radical has been identified in comets (Greenstein 1958;Ferrin 1977;Johnson et al 1983;Fray et al 2005), stars (Fowler & Shaw 1912;Lambert et al 1984), the Sun (Uitenbroek & Tritschler 2007), circumstellar shells (Wootten et al 1912;Wiedemann et al 1991;Bakker & Lambert 1998), interstellar clouds (Turner & Gammon 1975;Meyer & Jura 1985) and the integrated light of galaxies (Riffel et al 2007). The CN lines of the violet system were also identified in the spectra of the Red Rectangle nebula, HD 44179 (Hobbs et al 2004). The presence of CN in astronomical environments makes it a useful probe of C and N abundances, as well as isotopic ratios, which provide information on nucleosynthesis and chemical evolution (Wang et al 2004;Riffel et al 2007;Savage et al 2002).…”
Section: Introductionmentioning
confidence: 98%